2013
DOI: 10.1007/s13224-012-0244-7
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Among Unmarried Adolescents and Young Adults

Abstract: Objective(s) To determine the risk factors for pregnancy among unmarried adolescents and young adults. Method(s) Case-control study was done over a period of 2 years. Data collected from 181 unmarried abortion seekers and 181 unmarried non-pregnant controls (B24 years) attending three Medical Colleges of Kerala. Results Logistic regression analysis showed a strong association between unmarried adolescent pregnancy and lack of parental supervision and control (OR 8.74, P = 0.000), poor intra-family relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…13 Teenage pregnancy can bring about major health and social problems with unique medical and psychosocial consequences for the adolescent and society at large. 14 For instance, it prevents teenagers from achieving their full potential and enjoying their basic human rights. 15 The effect of teenage pregnancy also adversely affects future earning potential and leads to lifelong poverty.…”
Section: Introductionmentioning
confidence: 99%
“…13 Teenage pregnancy can bring about major health and social problems with unique medical and psychosocial consequences for the adolescent and society at large. 14 For instance, it prevents teenagers from achieving their full potential and enjoying their basic human rights. 15 The effect of teenage pregnancy also adversely affects future earning potential and leads to lifelong poverty.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown family connectedness to be protective against early sexual debut and involvement in high-risk sexual behaviour, 14 that family relationships affect the incidence of unplanned adolescent pregnancies 23 as well as condom use among young adults. 15 We have seen that the family microsystem, consisting of parents and siblings, can influence behaviour.…”
Section: Discussionmentioning
confidence: 97%
“…Adolescents are the most important target group in reproductive health programs [2] Additionally, more than other age groups, adolescents are more susceptible to substance abuse, smoking, alcohol, and engaging in risky behaviors, including unsafe sexual relationships [3]. These factors make adolescents vulnerable to numerous problems including infections, sexually transmitted diseases, especially HIV and hepatitis [4], pelvic inflammatory disease, infertility, ectopic pregnancy [5,6], unwanted pregnancies, illegal and unsafe abortion [7], unsafe deliveries, maternal and neonatal morbidity and mortality as well as unsafe motherhood [8]. These events affect not only the individual but also the family and society.…”
Section: Introductionmentioning
confidence: 99%